Multiple Domains in the Rhizobial Type III Effector Bel2-5 Determine Symbiotic Efficiency With Soybean - Ratu, Safirah Tasa Nerves; Hirata, Atsushi; Kalaw, Christian Oliver; Yasuda, Michiko; Tabuchi, Mitsuaki; Okazaki, Shin (Frontiers in Plant Science, 2021)
Bradyrhizobium elkanii utilizes the type III effector Bel2-5 for nodulation in host plants in the absence of Nod factors (NFs). In soybean plants carrying the Rj4 allele, however, Bel2-5 causes restriction of nodulation by triggering immune responses. Bel2-5 shows similarity with XopD of the phytopathogen Xanthomonas campestris pv. vesicatoria and possesses two internal repeat sequences, two ethylene (ET)-responsive element-binding factor-associated amphiphilic repression (EAR) motifs, a nuclear localization signal (NLS) and a ubiquitin-like protease (ULP) domain, which are all conserved in XopD except for the repeat domains. By mutational analysis, we revealed that most of the putative domains/motifs in Bel2-5 were essential for both NF-independent nodulation and nodulation restriction in Rj4 soybean. The expression of soybean symbiosis- and defence-related genes was also significantly altered by inoculation with the bel2-5 domain/motif mutants compared with the expression upon inoculation with wild-type B. elkanii, which was mostly consistent with the phenotypic changes of nodulation in host plants. Notably, the functionality of Bel2-5 was mostly correlated with the growth inhibition effect of Bel2-5 expressed in yeast cells. The nodulation phenotypes of the domain-swapped mutants of Bel2-5 and XopD indicated that both the C-terminal ULP domain and upstream region are required for the Bel2-5-dependent nodulation phenotypes. These results suggest that Bel2-5 interacts with and modifies host targets via these multiple domains to execute both NF-independent symbiosis and nodulation restriction in Rj4 soybean.